A framework for characterizing the ambient conditions experienced by light duty vehicles in the United States. Issue 2 (1st February 2022) - Moniot, Matthew; Lustbader, Jason; Wood, Eric; Lee, Byungho; Fink, Justin; Agnew, Scott
Abstract: The relationship between ambient conditions and light-duty vehicle energy consumption has been widely researched. Relatively little effort, however, has been dedicated to understanding representative ambient conditions a light-duty vehicle may experience. The framework introduced in this article provides a means of quantifying ambient conditions specific to light-duty vehicle operation by incorporating both when and where vehicles are driven. The analysis presented expands the literature beyond solely focusing on temperature; distributions for humidity, solar irradiance, and air density are also included. A procedure is presented that calculates the ambient condition distributions for each metric by relating open-source data sets describing representative vehicle utilization and representative ambient conditions. While this study explores ambient conditions related to light-duty vehicle utilization, the framework may also be applied to separate vocations. Finally, the article concludes with an example use case of the ambient condition weighting process. A binning methodology is introduced that facilitates insight into vehicle energy consumption in response to ambient conditions at the national and local levels while minimizing the number of tests or simulations required.